MULTIPLE INTELLIGENCES ON STUDENTS’ LEARNING OUTCOMES: DIFFERENTIATED LEARNING CONTEXT - Murtafiah, Muhimatul; Muniroh, Siti; Widiati, Utami (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This study explores the impact of various intelligences, learning styles, and linguistic abilities on English language proficiency among junior high school students in a differentiated learning context. Drawing on Howard Gardner's theory of multiple intelligences and previous research, this qualitative research aimed to investigate whether students' interests, motivation, and cognitive profiles influence their language learning outcomes. Data were collected through questionnaires and analyzed manually using tables. Findings reveal a significant correlation between students' interests, learning styles, linguistic intelligence, and English proficiency. While some students demonstrate exceptional performance, others exhibit diverse learning preferences and intelligence, challenging traditional notions of language acquisition. The study underscores the importance of differentiated instruction tailored to individual needs and preferences for optimizing language learning outcomes.